Developing Translation Rules for Converting Relational to Object Oriented Database Conceptual Schema - Ibrahim, Hamidah; Ki, Soon Lay; Mamat, Ali; Muda, Zaiton (Universiti Putra Malaysia Press, 2005)
A multidatabase is a confederation of pre-existing distributed, heterogeneous, and autonomous database system. Obviously, the integration process is essential in the effort of forming a distributed, heterogeneous database system. This process generally consists of two main phases, which are conceptual schema translation phase followed by the integration phase. This paper presents a translation approach to convert relational database schema to object-oriented database schema. The translation approach consists of a set of translation rules, which is based on inclusion dependencies, key attributes and types of attributes. A database schema translation tool prototype, called RETOO (RElational-ToObject- Qriented) is then developed based on the proposed translation approach. RETOO receives a relational database schema as input data and generates an object-oriented database schema as the output. The translation approach is not only able to maintain the semantics of the relational database schema, but also enhance the semantics of the translated object-oriented schema via objectoriented data modeling concepts.